PNOC's most innovative new and renewable energy system - Center for Social Concern and Action-De La Salle University, Manila (Animo Repository, 2001)
The Center for Social Concern and Action - College of Engineering, Abra Micro-Hydro project was recognized for having won first place, PNOC's Most Innovative New and Renewable Energy System during the Student Awards 2001 ceremonies.